ETHNOMATHEMATICS INTEGRATION IN MATHEMATICS EDUCATION: A CASE STUDY OF FORT ROTTERDAM IN MAKASSAR - Nur Wahidin Ashari; Fauziyyah Alimuddin (Pedagogy: Jurnal Pendidikan Matematika, 2024)
This research investigates the integration of ethnomathematics into mathematics education through a case study of Fort Rotterdam in Makassar. The urgency of this study lies in the recognition of the significance of ethnomathematics in enriching students' learning experiences and fostering cultural understanding in mathematics education. The study use a qualitative case study method, focusing on Fort Rotterdam as a historical and architectural landmark. Data collection involves observational techniques to examine the mathematical principles inherent in the fort's design and construction. Through systematic observation and analysis, the research aims to uncover how mathematical concepts are manifested in the architecture and layout of Fort Rotterdam, thereby illustrating the integration of mathematics into cultural artifacts. The findings reveal the intricate relationship between mathematics, culture, and history exemplified by Fort Rotterdam. Geometry, trigonometry, and other mathematical principles are intricately woven into the fort's structure, reflecting the practical applications of mathematics in historical contexts. This study underscores the importance of ethnomathematics in mathematics education, emphasizing its role in broadening students' perspectives and fostering a deeper understanding of the subject. In conclusion, the integration of ethnomathematics into mathematics education, as exemplified by the case study of Fort Rotterdam, offers valuable insights into the practical applications of mathematics within cultural contexts. By recognizing and appreciating the mathematical practices embedded in cultural artifacts, educators can enhance the relevance and significance of mathematics education, promoting cultural appreciation and understanding among students.